Non-invasive administration of poractant-α in neonatal respiratory distress syndrome via a supraglottic device in the clinical practice in a second level neonatal unit: comparison of LMA® vs iGel® devices.: Non-invasive administration of poractant-α in NRDS - Parmigiani, Stefano; Bevilacqua, Giulio (Acta Biomedica Atenei Parmensis, 2022)
Non-invasive pulmonary surfactant (SF) administration for neonatal respiratory distress syndrome (NRDS) is a development of administration of SF. Administration of SF via a supraglottic device (SGD) has been shown to be effective. Here the results of administration of SF in NRDS in infants requiring oxygen and nasal-CPAP (n-CPAP) via two types of SGDs, LMA® vs iGel®, in a second level Neonatal Unit are reported in a retrospective study.Results – Fourteen infants in the LMA®Group were matched with 21 comparable infants in the iGel® Group (g.a. ≥30 wks and b.w. ≥ 1,500 gr) presenting NRDS with fraction of inspired oxygen (FiO2) ≥ 0.25 – 0.6, requiring n-CPAP. All infants presented a significant improvement of PaO2/FiO2 ratio that was seen earlier in the iGel® Group vs the LMA® Group. There was no severe adverse effect during the maneuver with both SGDs. No baby died, No.2 required endotracheal intubation for a second dose of SF as by protocol, and No. 1 was transferred to a higher level of care.Conclusion – Non-invasive SF administration via SGD has been done effectively at a second level Neonatal Unit and very early in the course of the disease therefore limiting transfer of the baby without complications with both SGDs. Improvement in gas exchange was more rapid in the iGel®Group. This result needs confirmation. In our experience iGel® was easier to use than LMA®.